Novel organoids mode evaluating the food nutrition and safety: Current state and future prospects - Fengling Tan; Pengfei Cui; Siting Li; Yingxia Tan; Aijin Ma (Food Frontiers)
Abstract Food nutrition and safety are the cornerstones of food industry, and appropriate research models are crucial. Unlike traditional animal models, the novel organoid model with unique humanization and genome stability has attracted great attentions in food research. However, there lacks systematic review on the application of organoids in food research. This review compared the organoid model with traditional animal and two‐dimensional cell models, followed by a systemic evaluation of the organoid model in food nutrition and safety regarding foodborne pathogenic bacteria, functional food factors, toxicology, flavor perception, and so on. Furthermore, emerging micromachining technologies such as microfluidic technology and three‐dimensional (3D) bioprinting were analyzed to improve the microenvironment and maturity of organoids. Although organoids overcome some shortcomings associated with traditional models, there are still some challenges to simulate the in vivo microenvironment fully. The development direction of organoids is integrating advanced technologies such as microfluidic technology, novel biomaterial scaffold, and 3D bioprinting with multi‐organ coculture technology and multi‐scale real‐time monitoring systems. The innovative development of organoid technology is expected to provide a theoretical basis for developing future foods represented by cell‐cultured meat and synthetic biological foods and for the research of food nutrition and safety.